Effects of source-sink regulation and nodal position of the main crop on the sprouting of regenerated buds and grain yield of ratoon rice - He, Aibin; Jiang, Min; Nie, Lixiao; Man, Jianguo; Peng, Shaobing (Frontiers in Plant Science, 2023)
Ratoon rice (Oryza sativa L.) is the production of a second season rice that utilizes the dormant buds surviving on the stubble left behind after the harvest of the main crop. However, the sprouting mechanism of regenerated buds at separate nodes is rarely reported. Field experiments were conducted to examine the effects of leaf-cutting and spikelet thinning on the sprouting of regenerated buds at the separate node, the contributions of regenerated panicles at the separate node to the total grain yield in the ratoon crop, and the associated mechanism. The results showed that the contribution of separate node yields to the total grain yield in the ratoon crop was D2 (panicles regenerated from the 2nd node from the top) >D3 (panicles regenerated from the 3rd node from the top) >D4 (panicles regenerated from the lower nodes below the 3rd node), and the contribution of D2 and D3 made up approximately 80 % of the total yield in the ratoon crop. In addition, the effect of leaf-cutting treatment and spikelet-thinning treatment on the grain yield of ratoon season was mainly realized by regulating the relative contribution rate of D2 and D4 grain yield to the total yield of ratoon season. Further analysis indicated that the sprouting of regenerated buds at the D2 node was mainly affected by the content of CTK, while D3 was mainly regulated by GAs and CTK, and D4 was mainly regulated by ABA and CTK. However, only the CTK content in stems and buds was positively correlated with single bud length and bud number at each nodes. These results indicated that CTK might be the main signal regulating the sprouting of regenerated buds and the grain yield at separate nodes, which might change the transport of assimilates to stems and buds.